A Metal Matrix CNTS Modified Electrode Fabricated Using Micromachining-Based Implantation Method for Improving Sensitivity and Stability. (18th November 2013) - Wang, Yan; Ran, Chen; Yang, Yuan; Ding, Guifu; Wang, Hong
Abstract : The metal matrix carbon nanotubes modified electrode (MCME) has been fabricated by a novel process involving preparation of carbon nanotubes (CNTs)/polyimide (PI) composite film, wet, etching, sputtering, electroplating, and wet-etch releasing. Pretreated CNTs are dispersed in PI by mechanical ball milling and then CNTs solution is spin-coated on the substrate. The CNTs/PI composite film is etched away a layer of PI to expose tips of CNTs using buffering solution. These exposed tips of CNTs are covered by metal particles in sputtering process as metal seed layer, followed by metal supporting film formed by electroplating. The MCME is obtained after releasing PI film from the metal supporting film. The MCME shows well morphology of uniform distributional protruding tips of CNTs and increased electron transfer efficiency with strong bonding connection between CNTs and metal matrix, which greatly improves sensitivity and stability of the MCME. The oxidation peak of the MCME in cyclic voltammeter (CV) test is 1.7 times more than that of CNTs suspension spin-coated metal electrode (SCME). The decline of peak current of the MCME after fifty cycles is only 1.8% much less than 67% of the SCME. Better sensitivity and stability may be helpful for CNTs modified electrodes wide application for trace test of many special materials.